The Role of PUSPAGA in Preventing Child Marriage: A Case Study in Tuban Regency - Amanda Dwi Selvi Tahlilia; Vania Ardelia (International Conference on Psychology and Education (ICPE), 2025)
Child marriage remains a pressing issue in Indonesia, particularly in traditional communities such as Tuban Regency, East Java. This study explores the role of PUSPAGA (Family Learning Center) as a government initiative in reducing the incidence of child marriage through premarital counseling for marriage dispensation applicants. Using a qualitative case study method, data were collected through observation, interviews, and documentation at the Department of Social Affairs, Women’s Empowerment, and Child Protection in Tuban. Findings reveal that most applicants are aged 15–18 and have low educational backgrounds, with economic hardship, premarital pregnancy, and cultural norms being the main drivers of early marriage. PUSPAGA plays a crucial role in assessing the readiness of prospective underage couples and educating families about the psychological, social, and legal consequences of early marriage. The counseling process also serves as a social intervention that challenges patriarchal values and strengthens family resilience. The study underscores the importance of preventive psychosocial services in protecting children’s rights and promoting gender-sensitive development.